Laterally Positioned Flap with Subepithelial Connective Tissue Graft Modified One-Stage Procedure for the Treatment of Deep Isolated Gingival Recessions in Mandibular Incisors - Alvaro Francisco Bosco; Juliano Milanezi de Almeida; Belén Retamal-Valdes; Renata Tavares; Jessica M. Latimer; Diego Messina; Matheus Henke; Laura Gantes Rodrigues Dias; Thiago Marchi Martins (Hindawi Limited, 2021)
The laterally positioned flap (LPF) has been proposed as a promising treatment for isolated gingival recessions (GRs) in mandibular incisors. Several modifications have been proposed to reduce the risk of gingival recession (GR) at the donor tooth site. Therefore, the aim of this was to describe a modified one-stage procedure of performing the LPF associated with the subepithelial connective tissue graft (LPF + SCTG) with the modifications for the treatment of deep isolated GR in mandibular incisors. The modified one-stage technique (LPF + SCTG) is unique because it was presented being bilaminar with tunneled connective tissue graft (CTG) in the adjacent tooth and extended to the flap donor site, without a submarginal incision in the adjacent tooth, taking the entire band of the keratinized tissue (KT) into the flap. In addition, 3 clinical cases were described using this surgical technique. Three healthy patients with Cairo RT1 or RT2 GRs on teeth 31 or 41 were treated with the LPF + SCTG technique. Probing depth (PD), clinical attachment level (CAL), complete root coverage (CRC), mean root coverage (MRC), recession depth (RD), and keratinized tissue width (KTW) were assessed at baseline and in the follow-up periods of 18, 24, and 48 months, in the cases 1, 2, and 3, respectively. The LPF + SCTG with the modifications presented is a predictable approach for the treatment of deep isolated RT1 and RT2 GRs in mandibular incisors that are well positioned in the bone envelope with the presence of KTW adjacent to GR and adequate vestibule depth in the donor area of the flap.